International rankings and “roadmap”: questions and perspectives - Sergey G. Prokhorov; Anna A. Svirina (Высшее образование в России, 2022)
The paper deals with comparative analys is of international university rankings methodology and a complex of measures for Russian higher education development suggested by the Ministry of Education and Science of the Russian Federation. It is revealed that the “roadmap” for higher education development does not allow predicting improvement of national university ranking in international surveys. Some important directions for Russian university recognition by international educational society are suggested in the paper.